Analisis Kelengkapan Administrasi, Farmasetik dan Klinis pada Resep Obat Batuk di Apotek Mitra Sehat Banjarbaru Periode Juli s.d. Desember Tahun 2023: Study on Cough Medicine Prescriptions at Mitra Sehat Banjarbaru Pharmacy for the Period of July to Desember 2023 - Zakiah Zakiah; Hasniah Hasniah; Muhammad Fauzi (PharmaCine : Journal of Pharmacy, Medical and Health Science, 2025)
This study aims to assess the completeness of cough medicine prescriptions based on administrative, pharmaceutical, and clinical aspects at the Mitra Sehat Banjarbaru Pharmacy from July to December 2023. The method used was a descriptive non-experimental, with a retrospective approach to 138 prescriptions, using a total sampling technique. Data analysis used Microsoft Excel 2021 software, namely by entering the obtained data into Microsoft Excel with the final percentage results and displaying them in graphical form. The results of the analysis of the administrative aspects showed that the majority of prescriptions included administrative completeness in accordance with standards, such as the prescription date, patient data, drug name, signature, doctor's SIP number, and the doctor's signature or initials. However, incomplete patient data was found at 100%, namely patient name 0%, patient address 94%, patient date of birth 95%, medical record number 40%, patient age 79%, patient weight 96%, patient gender 99%. In terms of pharmaceutical aspects, the results showed a fairly high level of conformity in dosage form and drug compatibility, each reaching 100%. However, there was a discrepancy in dosage strength in 4% (5 prescriptions). The clinical aspects of this study showed that the majority of prescriptions listed the appropriate route of administration, reaching 99%. The most commonly prescribed drug by doctors was Guiafenesin, at 56% (77 prescriptions). This study concluded that of the 138 prescriptions analyzed, the majority of prescriptions fulfilled most administrative aspects, such as the patient's name, the doctor's Practice License (SIP) number, and the doctor's signature or initials. In terms of pharmaceutical aspects, the results showed a fairly good conformity, in terms of dosage form and drug compatibility, reaching 100%. The clinical aspects of this study showed a completeness result reaching 99%. Nevertheless, it is recommended that pharmacies strengthen prescription review protocols and increase pharmacist supervision to prevent medication errors and improve patient safety in pharmaceutical services. Keywords: Pharmaceutical services; Administrative aspects; Pharmaceutical aspects; Clinical aspect.